Quality of Scholastic Tests in the New Student Admission Selection (SPMB) at Universitas Negeri Surabaya in the 2023 Academic Year - Tri Rijanto; Edy Sulistyo; Joko; Puput Wanarti Rusimamto (Kirana Publisher (KNPub), 2026)
Scholastic tests play a critical role in university admission systems, serving as gatekeeping mechanisms that influence both institutional quality and educational equity. Despite their widespread use, empirical evaluations of institutional admission test quality remain limited, particularly in developing country contexts. This study aimed to comprehensively evaluate the psychometric quality of the Scholastic Potential and Basic Ability Test (SPMB) administered at Universitas Negeri Surabaya during the 2023 academic year, examining reliability, item difficulty, discrimination indices, and distractor effectiveness. A quantitative descriptive research design using ex-post facto analysis was employed. The study analyzed test response data from 270 candidates who completed the 45-item SPMB, consisting of three subtests: Verbal Ability (15 items), Numerical and Reasoning Ability (15 items), and Figural Comprehension Ability (15 items). Data analysis utilized Classical Test Theory frameworks, calculating Kuder-Richardson Formula 20 (KR-20) reliability coefficients, item difficulty indices (p-values), point-biserial discrimination coefficients (rpbis), upper-lower 27% discrimination indices (D), and distractor effectiveness metrics using SPSS 26.0 and ITEMAN 4.3 software. The total test demonstrated good internal consistency reliability (KR-20 = 0.84) with a mean score of 25.84 (SD = 6.78, 57.42% of maximum). Approximately 62% of items exhibited optimal moderate difficulty (0.40 ≤ p < 0.80), and 73% demonstrated good-to-excellent discrimination (rpbis ≥ 0.30). However, three items showed poor discrimination (rpbis < 0.20), 22 distractors were non-functional (16.30%), and six distractors exhibited problematic positive discrimination (4.44%). Subtest reliabilities ranged from 0.70 to 0.75, classified as acceptable. The SPMB demonstrated generally satisfactory psychometric quality but requires targeted improvements through systematic item revision, enhanced item writer training, and continuous quality monitoring. Findings provide actionable guidance for evidence-based test refinement and contribute empirical evidence to admission testing literature in Southeast Asian higher education contexts.